Breaking the mold with RNA—a “RNAissance” of life science - Charles H. Jones; John R. Androsavich; Nina So; Matthew P. Jenkins; Derek MacCormack; Andrew Prigodich; Verna Welch; Jane M. True; Mikael Dolsten (npj Genomic Medicine, 2024)
Abstract In the past decade, RNA therapeutics have gone from being a promising concept to one of the most exciting frontiers in healthcare and pharmaceuticals. The field is now entering what many call a renaissance or “RNAissance” which is being fueled by advances in genetic engineering and delivery systems to take on more ambitious development efforts. However, this renaissance is occurring at an unprecedented pace, which will require a different way of thinking if the field is to live up to its full potential. Recognizing this need, this article will provide a forward-looking perspective on the field of RNA medical products and the potential long-term innovations and policy shifts enabled by this revolutionary and game-changing technological platform.